Comparison of Antioxidant Activity Testing of Rosemary Leaves Using the DPPH Method - Ardian, Muhammad Nur; Wahyuningsih, Sri; Sudarni, Dyan Hatining Ayu (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2025)
The ability of rosemary leaf extract to scavenge free radicals was tested using the DPPH method in this research. Rosemary leaves were selected based on their natural richness in antioxidant compounds such as polyphenols and flavonoids. The test results showed that the ethanol extract, ethyl acetate fraction, and n-hexane fraction all exhibited very strong antioxidant potential, with values below 50 ppm. The ethanol extract was the most potent with an IC₅₀ of 23.98 ppm, followed by the ethyl acetate fraction with an of 26.60 ppm and the n-hexane fraction with an of 27.95 ppm. The superiority of the ethanol extract is attributed to its ability as an optimal polar solvent for dissolving phenolic compounds. These compounds play a crucial role in stabilizing free radicals through hydrogen/electron donation, as well as resonance mechanisms.